Politics and the implementation of the New Poor Law: the Nottingham workhouse controversy, 1834-43 - Beckett, John (Maney Publishers, 2016)
The Nottingham workhouse case was a test of the resolve both of the Poor Law Commissioners appointed to administer the post-1834 New Poor Law, and of the strength of the Whig interest in the town’s municipal and parliamentary elections. All eyes were on the implementation of the legislation in Nottingham, partly because of the influential thinking of local administrators such as Absolem Barnett, and partly because the government needed evidence that the system of unions and workhouses set up after 1834 would actually work in industrial towns. The Nottingham case showed only too clearly that the key issue was the trade cycle, and fluctuations in the town’s hosiery and lace trades made it almost impossible to implement the terms of the legislation fully. The key battle was fought over the decision to build a new workhouse, which the Whigs favoured and the Tories resisted.